Relationship Between Leapfrog Safe Practices Survey and Outcomes in Trauma - Glance, Laurent G. (2011)
OBJECTIVE: To examine the association between hospital self-reported compliance with the National Quality Forum patient safety practices and trauma outcomes in a nationally representative sample of level I and level II trauma centers. DESIGN: Retrospective cohort study using the Nationwide Inpatient Sample. SETTING: Level I and level II trauma centers. PATIENTS: Trauma patients. MAIN OUTCOME MEASURES: Multivariate logistic regression models were estimated to examine the association between clinical outcomes (in-hospital mortality and hospital-associated infections) and the National Quality Forum patient safety practices. We controlled for patient demographic characteristics, injury severity, mechanism of injury, comorbidities, and hospital characteristics. RESULTS: The total score on the Leapfrog Safe Practices Survey was not associated with either mortality (adjusted odds ratio [aOR], 0.92; 95% confidence interval [CI], 0.79–1.06) or hospital-associated infections (1.03; 0.82–1.29). Full implementation of computerized physician order entry was not associated with reduced mortality (aOR, 1.03; 95% CI, 0.75–1.42) or with a lower risk of hospital-associated infections (0.94; 0.57–1.56). Full implementation of intensive care unit physician staffing was also not predictive of mortality (aOR, 1.13; 95% CI, 0.90–1.28) or of hospital-associated infections (1.04; 0.76–1.42). CONCLUSION: In this nationally representative sample of level I and level II trauma centers, we were unable to detect evidence that hospitals reporting better compliance with the National Quality Forum patient safety practices had lower mortality or a lower incidence of hospital-associated infections.